2013
DOI: 10.7567/jjap.52.11nj04
|View full text |Cite
|
Sign up to set email alerts
|

New Cu(TiIrNx) Alloy Films for Solder Bump Flip-Chip Application

Abstract: A new copper alloy that shows fine thermal stability and adhesion to the substrate is developed in this study by cosputtering Cu, Ti, and Ir on a barrierless Si substrate within an Ar/N2 gas atmosphere to form a Cu(TiIrN x ) film. To reduce manufacture cost, we can replace both the wetting and diffusion layers underneath flip-chip solder joints in conventional under bump metallurgy with this thermally stable film, which exhibits weak, if any, interactions between the film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The bind structure of Cu(TiIrN x ) already shown in the XPS profile in Ref. 34 verifies that the Ti-N and Ir-N contained in the TiIrN x phase form a bind structure that prevents oxidation, helps in heat dissipation, and is beneficial to an LED's heat dissipation in application.…”
Section: Methodsmentioning
confidence: 56%
“…The bind structure of Cu(TiIrN x ) already shown in the XPS profile in Ref. 34 verifies that the Ti-N and Ir-N contained in the TiIrN x phase form a bind structure that prevents oxidation, helps in heat dissipation, and is beneficial to an LED's heat dissipation in application.…”
Section: Methodsmentioning
confidence: 56%
“…19) The degree of Cu oxidation is strongly related to the degree of outward diffusion of the additives. Previous studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] have shown that Cu(ReN) alloy films 25) are thermally stable up to 730 °C. Transition-metal nitrides have also received considerable attention owing to their desirable properties for many applications.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] When the electric field strength exceeds 2.7 MV/cm, the leakage current for the pure Cu gates in the capacitors increases markedly owing to a large amount of Cu that diffused through SiO 2 during annealing. At 2 MV/cm, the leakage current of the Cu(GeN x ) film (2.09 © 10 ¹10 A/cm 2 ) is lower than those of the Cu(Ge) (1.86 © 10 ¹8 A/cm 2 ), Cu(WN) (4.9 © 10 ¹9 A/cm 2 ), 11) Cu(MnN) (3.83 © 10 ¹10 A/cm 2 ), 8) Cu(Mo) (3.8 © 10 ¹8 A/cm 2 ), 12) and pure Cu (1.6 © 10 ¹7 A/cm 2 ) films, 10) confirming the Cu(GeN x ) film's excellent thermal stability and confirming its role in barrierless metallization. The results are consistent with the SIMS results shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The alloying of Cu with insoluble components has attracted the attraction of many researchers owing to its many for several industrial applications and is crucial in materials science. For example, Cu(RuN x ), films were developed and reported in 2007 and 2010; [5][6][7][8][9][10] previous studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have shown that Cu(ReN) 13) alloy films are thermally stable up to 730 °C. Iijima et al and Dixit et al developed Cu-Mn alloy films that can be applied to the fabrication of interconnects in semiconductor manufacture.…”
Section: Introductionmentioning
confidence: 99%